Degradation of dyes using crude extract and a thermostable and pH-stable laccase isolated from Pleurotus nebrodensis. Issue 4 (5th August 2016) - Yuan, Xianghe; Tian, Guoting; Zhao, Yongchang; Zhao, Liyan; Wang, Hexiang; Ng, Tzi Bun
Abstract : Three laccase isoenzymes (Lac1, Lac2 and Lac3) have been purified to homogeneity from Pleurotus nebrodensis in our previous study. Lac2 was shown to be the dominant isoform, capable of oxidizing the majority of laccase substrates and manifesting good thermostability and pH stability. Hence, Lac2 was selected to decolourize structurally different dyes and the colour removal efficiencies of Lac2 and the crude extract of P. nebrodensis were compared . By monitoring the λ max of the reaction system during the course of biotransformation, clear hypsochromic shifts were observed for most of the dyes examined, illustrating that at least one peak disappeared as a result of laccase treatment. In general, Lac2 was more efficient within a short time (1 h) and the crude extract, in general, could achieve similar or even higher efficiency when the duration of treatment was extended to 24 h. Malachite green (MG) was chosen to study the detoxifying potential of Lac2, because of the relatively simple structure and high toxicity of the dye towards microorganisms. The toxicity of MG towards both bacteria ( Bacillus subtilis, Bacillus licheniformis, Pseudomonas fluorescens and Escherichia coli ) and fungi ( Fusarium graminearum and Trichoderma harzianum ) was dramatically decreased and the potential mechanism was estimated by GC–MS as to remove four methyl groups firstly and the two newly formed amine groups would be degraded or polymerized further. The present study facilitates an understanding of the application of P. nebrodensis laccases and furnishes evidence for the safety of their utilization in the treatment of wastewater emanating from textile industries.